SMART BRT ITERA Management: A Pilot Project of Indonesia's Inclusive Bus Campus System - Saraswati, Zenia F; Wijayanti, Goldie Melinda; Juanda, Denny (Journal of Sustainability Perspectives, 2021)
Sustainable transportation service is not only about reducing exhaust emissions but about its impact on society.This work seeks to analyze the potential of ITERA Smart Bus Rapid Transit (Smart BRT ITERA) as a regional campus buses in creating the accessibility needed by the wider community, affordable in terms of tariffs, efficient and supporting economic development and reducing emissions and waste generated in the Institut Teknologi Sumatera (ITERA) in Lampung, Indonesia. As a commitment to sustainability by planning Smart BRT ITERA form of collaboration with the Ministry of Transportation of the Republic of Indonesia. ITERA, in this case, acts as the operator of 10 buses grants by the Ministry to serve this activity. It is hoped that this project can become a best practice for other universities in Indonesia